Replication kinetics of novel swine influenza A viruses: an approach to vaccine production - Tapia, Rodrigo; Medina, Rafael; Neira, Victor (Austral Journal of Veterinary Sciences, 2024)
Novel swine Influenza A viruses (IAVs) have been described in South America. The objective of this study was to evaluate the replication kinetics of novel swine IAVs as a first step in vaccine production. Different swine IAV lineages (H1N1, H1N2, and H3N2), infection doses (MOI: 1, 0.1, 0.01, 0.001, 0.0001, and 0.00001), harvest times (every 12 h), and substrates (MDCK and Vero cells) were used. For all IAV strains, MDCK cells were the most efficient substrate, generating titers of ≥128 HAU/50 μL with an MOI of 0.00001 at 60 h post-infection. These data may be useful in vaccine-producing laboratories.